2008
DOI: 10.1016/j.apmr.2007.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Between High- and Low-Frequency Transcutaneous Electric Nerve Stimulation Delays the Development of Analgesic Tolerance in Arthritic Rats

Abstract: Objective-To investigate whether repeated administration of modulating frequency transcutaneous electric nerve stimulation (TENS) prevents development of analgesic tolerance.Design-Knee joint inflammation (3% carrageenan and kaolin) was induced in rats. Either mixed or alternating frequency was administered daily (20min) for 2 weeks to the inflamed knee under light halothane anesthesia (1%-2%). Setting-Laboratory. Animals-Adult male Sprague-Dawley rats (N=36).Intervention-Mixed-(4Hz and 100Hz) or alternating-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 49 publications
6
63
0
3
Order By: Relevance
“…Our previous studies show that tolerance to repeated application of high and low frequency TENS can be prevented by blockade of systemic NMDA receptors during the TENS application, and this prevents the cross-tolerance at spinal opioid receptors [36]. Further, combining high and low frequency TENS delays the onset of tolerance by one week [14]. Together with the findings that CCK receptor activation prevents tolerance to repeated TENS, these data suggest there are multiple parallel systems that contribute to tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies show that tolerance to repeated application of high and low frequency TENS can be prevented by blockade of systemic NMDA receptors during the TENS application, and this prevents the cross-tolerance at spinal opioid receptors [36]. Further, combining high and low frequency TENS delays the onset of tolerance by one week [14]. Together with the findings that CCK receptor activation prevents tolerance to repeated TENS, these data suggest there are multiple parallel systems that contribute to tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were also tested for knee joint withdrawal threshold using a pair of forceps (tweezer) applied to the knee joint as previously described [14,56]. The forceps were equipped with two strain gauges to measure force.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically blockade of NMDA-glutamate receptors or CCK receptors in the spinal cord prevents analgesic tolerance to both LF and HF TENS [45,46]. Analgesic tolerance can also be prevented by modulating between LF and HF TENS within a treatment session [47], or by increasing intensity of TENS daily [48]. Thus, animal studies suggest TENS tolerance can be delayed with pharmacological methods as well as with non-pharmacological modulation of TENS parameters.…”
Section: Factors That Directly Affect Tens Efficacymentioning
confidence: 99%
“…The options to adjust the stimulation patterns or waveforms are also available in most TENS devices. A recent study reported that alternating low and high frequencies were helpful in slowing the development of tolerance in arthritic rats [17] . Thus, the modulating stimulation patterns may be an important approach for preventing tolerance.…”
Section: Discussionmentioning
confidence: 99%